PENGEMBANGAN BUDAYA LITERASI DIGITAL MEDIA PEMBELAJARAN MENGGUNAKAN APLIKASI CANVA DISEKOLAH DASAR PADA KURIKULUM MERDEKA BELAJAR - Raudhatul Jannah; Nur Azmi Alwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Learning in the 21st century is full of creativity. relevant to the opinion ofrahmawati, farida., & atmojo (2021) that 21st century learning is based oninformation and communication technology and is constructionist. with that,teachers are required to develop interesting and student-centered learning. in thisera, teachers act as facilitators. Literacy is defined as the ability to read and writecharacters while media means an intermediary that can take the form of objects,people or events. so it can be concluded that media literacy is the ability to search,study, and utilize various forms of media. This research uses library research,namely looking for research sources by collecting from several literatures sourcedfrom journals, books and other sources. Digital literacy is a person's ability or skillto process, analyze, and evaluate technology-based media. With the currentcondition of literacy, Indonesia's literacy level is still low due to a lack ofunderstanding of the correct basic literacy concepts or it could also be becausethe implementation of literacy implementation is less supportive and sustainable.With a low reading culture, Canva can be used as a tool or media that can attractliteracy culture with attractive designs. The media engaged in the field of digitalliteracy culture is canva. The use of canva application media can develop aliteracy culture digital elementary school students so that it can have a positiveimpact, students are more interested and enthusiastic about participating inlearning activities, making it easier for students to get information, expressingstudent creativity so that they can develop knowledge and creativity.